EFFECT OF SELECTED PILATES EXERCISES ON PHYSIOLOGICAL CHARACTERISTICS OF OBESEPEOPLE - Tyagi, Rahul; Kumar, Pravin (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the present study was to find out the effect of selected Pilates exercises on the physiological characteristics of obese people. The total sample of 60 males between the age groups of 20 and 45 years was selected and divided into two groups, i.e., 30 in the experimental group and 30 in the control group, from the general population of Muzaffarnagar, Uttar Pradesh. In the present study, a purposive-random sampling technique was employed to select the sample for measuring resting heart rate, systolic blood pressure, diastolic blood pressure, & lung capacity. The subjects underwent training for 24-weeks with the Pilates exercises. The difference in the mean of each group for selected variables was tested for the significance of the difference by paired „t‟ test. The level of significance was set at 0.05. The result was found that the effect of selected Pilates exercises was significant resting heart rate, systolic blood pressure, diastolic blood pressure, & lung capacity of the experimental group as compared to the control group.